.

  1-2
  3-4
  4-5
  6
  7
  8

  1
  1-2
  2-3
  4
  5
  6
  7
  8
  9

       

           
  " "
: . .

 

" "
: . .

4.

 

4.1.

 

. () .

, (, ) ( ). . , , .

δ, z , .

t1 t2 ( ).

. (3.52), , ∂t/∂τ=0. , , , . (3.52) (3.61):

d2t/dz2 = 0. (4.1)

:

dt/dz = C1; dt = C1 dz, (4.2)

t = C1z + C2, (4.3)

C1 C2 , , , . .:

1) z = 0 t = t1,

2) z = δ t = t2. (4.4)

(4.3) , z . , t1 < t2. .

(4.4) (4.3),

C2 = t1, (4.5)

, , (4.5)

t2 = C1δ + t1, (4.6)

C1 = (t2 - t1)/ δ. (4.7)

C1 C2 (4.3), ,

t = t1 + z (t2 - t1)/ δ. (4.8)

(4.8) .

(4.4) (4.8)

(t2 - t1)/ δ = (t2 - t1)/ δ, (4.9)

, (3.9),

q/λ = - (t2 - t1)/ δ = (t2 - t1)/ δ (4.10)

q = λ (t1 - t2)/ δ. (4.11)

. , n δ1, δ2, ..., δn λ1, λ2, ..., λn. . ( ) , , - (.4.1.). : t1 tn+1. . , , t1 t4, t2 t3.

 

. 4.1. [8]

 

, , , , , .

(4.1). (4.11). (4.11), , n , :

q = (λ1/δ1) (t1 - t2),

q = (λ2/δ2) (t2 - t3),

.

q = (λn/δn) (tn - tn+1). (4.12)

(4.12) :

t1 - t2 = q δ11,

t2 - t3 = q δ22,

..

tn - tn+1 = q δnn. (4.13)

(4.13)

t1 - tn+1 = q1/λ1 + δ2/λ2 + + δnn). (4.14)

:

q = (t1 - tn+1)/(δ1/λ1 + δ2/λ2 + + δnn). (4.15)

(4.16)

 

i .

(4.14) tn+1,

tn+1 = t1 - q1/λ1 + δ2/λ2 + + δn/λn). (4.17)

(4.8).

(4.17), . n i- , . ,

t2 = t1 - q (δ11), (4.18)

t3 = t1 - q1/λ1 + δ2/λ2). (4.19)

n + 1 = 2, n + 1 = 3

q (4.15) .

. ,

ti, z = ti - q(zii), (4.20)

zi i- , ti.


  4-5
  7

Copyright 2002-2007 .                                                                                                            e-mail: mailto:web-msuee@rambler.ru
: ..
: ..